O conhecimento e as atitudes das famílias de pacientes em tratamento em tuberculose na atenção primária à saúde - Queiroz, Ana Angélica Rêgo de (2012)
This study thus sought to examine knowledge about TB and attitudes of patients families in disease treatment in Primary Health Care in Natal- RN. To this end, a cross-sectional study was undertaken through a questionnaire with families of patients diagnosed with TB and follow up by APS from Natal. The study subjects were recruited from a non-probabilistic way, by convenience, contemplating a sample of 50 families. Among the criteria considered for inclusion of subjects, older than 18 years were considered, as well as residing with the TB patient and in Natal and availability to participate in the research. Data collection was performed by own researcher and an assistant, through a questionnaire with families of patients diagnosed with TB following the double independent digitalization of data. In the analytical phase, was initially conducted an exploratory phase and univariate data, with description of the position measurements (mean, median, mode) and dispersion (confidence interval and standard deviation). In bivariate analysis, it was conducted an intersection of dependent variables of knowledge e and changes of attitude dichotomous, with each of the independent variables, using contingency tables and calculating the chi-square test and, when appropriate, the Fisher exact test. In 2x2 tables, calculated the odds ratio (OR) with confidence intervals of 95% (95% CI). From the selected sample, 43 (86%) subjects were female, average age and median respectively of 46.64 and 46.50 years, 25 (50%) had elementary school. The knowledge expressed by family members about TB was considered satisfactory. However, the lack of interest of the family (54%) in seeking information about tuberculosis; the wrong way of reply in relation to the organism causing the disease (64%); the water content (62%) and contaminated food (54% ) as a means of spreading TB was a weakness identified in the investigation. Regarding the time of transmission, 90% of respondents indicated not know or answered wrong. From investigated independent variables, only two were associated with lack of knowledge of TB, and they did not have religion (OR: 0.146, 95% CI: 0.027 to 0.800) and income below 1, 7 minimum wages (OR: 0.155, 95% CI: 0.029 to 0.813). Thus they seem to exercise a protective effect on this outcome. As for the changes in attitude, most of the found variables had no association with statistical significance, except no internet access (OR: 0.212, 95% CI: 0,048-0, 935). Most attitudes were positive in relation to TB patient. Results have demonstrated weaknesses in TB care, which has taken on a more individual and welfare character. Data not only express health outcomes produced by health services, but also the political and social situation of the families that are affected by TB